Analisys of long non-coding RNAs transcribed from telomeres during adipocyte differentiation - Ruiz, Marina Cintia (2021)
Long non-coding RNAs transcribed from telomeres, known as TERRA (telomeric repeat containing RNA), are associated with telomere and genome stability. Oxidative stress damages biomolecules and telomeres are particularly prone to be damaged, thus it is relevant their protection to avoid telomere dysfunction. We have previously shown that the level of TERRAs increased in response to oxidative stress as a mechanism of telomere protection.